Impact of Strand Number on Parallel β‐Sheet Stability. Issue 48 (12th October 2015) - Kung, Vanessa M.; Cornilescu, Gabriel; Gellman, Samuel H.
Abstract: We have examined whether parallel β‐sheet secondary structure becomes more stable as the number of β‐strands increases, via comparisons among peptides designed to adopt two‐ or three‐stranded parallel β‐sheet conformations in aqueous solution. Our three‐strand design is the first experimental model of a triple‐stranded parallel β‐sheet. Analysis of the designed peptides by nuclear magnetic resonance (NMR) and circular dichroism (CD) spectroscopy supports the hypothesis that increasing the number of β‐strands, from two to three, increases the stability of the parallel β‐sheet. We present the first experimental evidence for cooperativity in the folding of a triple‐stranded parallel β‐sheet, and we show how minimal model systems may enable experimental documentation of characteristic properties, such as CD spectra, of parallel β‐sheets. Abstract : More strands, more stable : The first experimental model of a triple‐stranded parallel β‐sheet was designed. Analysis by NMR and circular dichroism spectroscopy offers the first experimental evidence that increasing the number of β‐strands from two to three increases the stability of the parallel β‐sheet.